Psychosocial problems of students and perceived motivation styles in Sekolah Menengah Kebangsaan Muara Tuang, Kota Samarahan, Sarawak - Gan, We Ling (1999)
This study attempted to identify the psychosocial problems experienced by secondary school students in Kota Samarahan, Sarawak, as well as their perceived parents' motivation styles. The psychosocial problem subscales identified through factor analysis were aggressive behavior, delinquent behavior, social problem, depression, withdrawn, psychosomatic complaint, destructive behavior and eating disorder.